Spodoptera exigua (Hubner) (Lepidoptera: Noctuidae) Fitness and Resistance Stability to Diamide and Pyrethroid Insecticides in the United States - Marcelo M. Rabelo; Izailda B. Santos; Silvana V. Paula-Moraes (Insects, 2022)
In the United States, beet armyworm resistance to both chlorantraniliprole and bifenthrin insecticides was first reported in 2020. Here we examined beet armyworm fitness and stability of resistance to chlorantraniliprole and pyrethroid insecticides since knowledge of the stability of resistance is a crucial aspect when recommending rotation of insecticides with different mode of action. Concentration-mortality bioassays were performed with field and laboratory susceptible populations. The F2, F13, and F27 generations of the field-derived population, maintained in the laboratory without insecticide, were exposed to commercial formulations of bifenthrin and chlorantraniliprole using the leaf-dip bioassay method (IRAC n. 007). Insects from F27 had the fitness components (survival, body weight, development time) documented and compared by LSM in each insecticide concentration tested. The resistance ratio to chlorantraniliprole reached 629, 80, 15-fold at F2, F13, and F27, respectively. These results contrast with an over 1000-fold resistance ratio to bifenthrin in all generations. The field-derived population had fitness reduced by chlorantraniliprole, but not by bifenthrin. In summary, the resistance of beet armyworm to bifenthrin was stable with no shift in fitness. In contrast, resistance to chlorantraniliprole was not stable through the generations kept in the laboratory without selection pressure, likely due to fitness cost.